Nasal Disorders: A Comprehensive Overview (Homoeopathy for All, 2024)
Nasal disorders encompass a  wide range of conditions affecting  the nasal cavity, sinuses, and  surrounding structures. They can  significantly impair respiratory  function, sense of smell, and overall  quality of life. These disorders  range from common issues like  allergic rhinitis and sinusitis to more  complex conditions such as nasal  polyps and structural deformities.  The nose plays a critical role in  filtering, humidifying, and warming  the air we breathe, so any disruption  in its function can have widespread  effects on respiratory health.
Keywords: Cystic Fibrosis; Asthma; Pollutants; Dental Infections